O processo de reelaboração do fazer pedagógico de uma professora de inglês: construindo um ensino que faz sentido - Valdeni da Silva Reis (Universidade Estadual Paulista Júlio de Mesquita Filho, 2013)
Very commonly the practice of a foreign language teacher is based on isolated structures, thus directing students' attention only to formal aspects of the language (WILLIAMS, 2001). This fact generates a decontextualized lesson where the teacher is the center of his/her practice and a series of activities is proposed in a "mechanical" way without creating real possibilities to develop students' learning. The central aim of this paper is to investigateother possibilities of pedagogical practice grounded in meaningful communication, which fosters learning. In order to do so, theoretical concepts concerning the input and output; the focus on the forms and focus on form (FonF); teaching under a meaningful perspective and the teaching and learning of a foreign language representations are discussed. Accordingly, data from a collaborative action research that emerges from the desire of an English teacherto discover a new possibility for her pedagogical practice is presented and discussed.